Comparison of nursing workload in a Pediatric Intensive Care Unit estimated by three instruments - Velozo, Kelly Dayane Stochero; Costa, Caroline Abud Drumond; Tonial, Cristian Tedesco; Crestani, Francielly; Andrades, Gabriela Rupp Hanzen; Garcia, Pedro Celiny Ramos (Revista da Escola de Enfermagem da USP, 2021)
Objective: To compare the nursing workload using the Nursing Activities Score (NAS), Therapeutic Intervention Scoring System-28 (TISS-28) and Nine Equivalents of Nursing Manpower Use Score (NEMS) instruments in children admitted to a Pediatric Intensive Care Unit in a university hospital. Method: A prospective cohort study performed in a Pediatric Intensive Care Unit, with a sample formed of all children hospitalized during the study period. Nursing workload was evaluated using the TISS-28, NEMS and NAS instruments, and further divided into two groups: Group 1 forming a category of basic activities items and Group 2 forming a category of other support and intervention activities. Results: The sample consisted of 490 Pediatric Intensive Care Unit admissions, totaling 4617 observations. NAS presented the best estimate of total working hours. TISS-28 and NEMS showed better agreement and the results showed strong correlations between NAS and TISS-28 and between NEMS and TISS-28. In Group 1 (basic activities), NAS(1) and TISS-28(1) showed moderate correlation, in Group 2 (specialized activities) the three instruments showed strong correlations. Conclusion: NAS stood out in the evaluation of nursing workload and showed good correlation and agreement with the TISS-28.